APLIKASI KOMBINASI TEPUNG DAUN GAMAL DAN TELUR PADA PAKAN KOMERSIAL TERHADAP KUALITAS PAKAN DAN EFISIENSI PAKAN IKAN NILA NIRWANA (Oreochromis niloticus) - Islama, Dini; Nurhatijah, Nurhatijah; Rahmi, Ismi; Ibrahim, Yusran; Saputra, Fazril; Diansyah, Sufal (Universitas Teuku Umar, 2020)
The objective of the present study was to evaluate the application of a combination of gamal leaf flour and eggs in commercial feed on the feed quality and feed efficiency of nirwana tilapia (Oreochromis niloticus). The completely randomized design method was used in this study with four treatments and four replications. The treatments studied were pellet without application of combination of gamal leaf flour and eggs (P0), pellet with combination gamal leaf flour 10 % / kg of feed and eggs (P1), pellet with combination gamal leaf flour 15 % / kg of feed and eggs (P2) and pellet with combination gamal leaf flour 20 % / kg of feed and eggs (P3). Nirwana tilapia fish seed stocking density was 1 individu/l with the length of 3-4 cm. The culture period of fish farming was 50 days. The ANOVA test showed that the commercial feed with the application of a combination of gamal leaf flour and eggs gave significant effect on the feed efficiency and specific growth rate of nirwana tilapia. The highest feed protein content was obtained in the P1 treatment of 30.17%. The smell of feed produced in all treatments tended to be strong and brown. The durability of feed in water which was almost close to control was treatment P1. The best dose to increase feed quality, feed efficiency and of nirwana tilapia seed is pellet with combination gamal leaf flour 10 % / kg of feed and eggs (P1).